PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADAREKTORAT UNIVERSITAS KHAIRUN TERNATE - Sarinita Sugiarto (Jurnal Manajemen Sinergi, 2015)
his study aims to explore to Work Discipline and Supervision happens At University Rector KhairunTernate. Exploration of labor discipline and supervision is done by using quantitative methods.Khairun University is one of the Institute of Higher Education is responsible for providing education.Based on the results of research work discipline and supervision are affected by the performance ofemployees.Work discipline and supervision that occurred At the University Rector office KhairunTernate thatcame not timely and home offices are not timely and the lack of monitoring, and the lack of guidanceand, given the lack of direction which could be one of the causes of high and low indicators ofemployee performance.This negative image of the effect on competition between universities on the unit's employees tofurther improve the performance of employees. Alternative efforts to address labor discipline andsupervision At the University Rector Khairun Ternate is to further improve work discipline effort toalways obey the regulations and supervision of such monitoring and inspection jobs directly as wellas more effective and efficient in conducting direct guidance and direction set by the UniversityKhairun Ternate.